Communication—Prediction of Thermal Issues for Larger Format 4680 Cylindrical Cells and Their Mitigation with Enhanced Current Collection. Issue 16 (29th December 2020) - Tranter, T. G.; Timms, R.; Shearing, P. R.; Brett, D. J. L.
Abstract : The paper numerically explores the electrochemical and thermal behaviour of a larger format 4680 cylindrical cell recently proposed by Tesla and explains the need to go "tabless." An idealized spiral geometry is used for 2D simulations with the traditional tab-based current collection method and a new continuous current collection method compared. The new design is found to mitigate the ohmic losses experienced around the "jelly-roll" current collectors which are significant for the traditional tabbed case, thus leading to higher efficiency and capacity and reduced heat production.